2009
DOI: 10.1111/j.1439-0523.2008.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of maize (Zea mays) stay‐green traits and their relationship to yield

Abstract: A maize genetic linkage map derived from 115 simple sequence repeat (SSR) markers was constructed from an F 2 population. The F 2 was generated from a cross between a stay-green inbred line (Q319) and a normal inbred line (Mo17). The map resolved 10 linkage groups and spanned 1431.0 cM in length with an average genetic distance of 12.44 cM between two neighbouring loci. A total of 14 quantitative trait loci (QTL) were detected for stay-green traits at different postflowering time intervals and identified by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 36 publications
7
67
1
Order By: Relevance
“…Our results were in accordance with Almeida et al (2014) who observed that genetic variance was reduced for grain yield and increased for ASI under drought stress. Significant negative correlations between ASI and yield in this study were congruent with other findings (Bolanos & Edmeads, 1996;Zheng et al, 2009;Almeida et al, 2014).…”
supporting
confidence: 82%
“…Our results were in accordance with Almeida et al (2014) who observed that genetic variance was reduced for grain yield and increased for ASI under drought stress. Significant negative correlations between ASI and yield in this study were congruent with other findings (Bolanos & Edmeads, 1996;Zheng et al, 2009;Almeida et al, 2014).…”
supporting
confidence: 82%
“…Climate change is expected to increase the frequency and severity of heat stress and drought events (Ahuja et al 2010;Long and Ort 2010). Avoidance of senescence under stress (stay-green) has been associated with maintained yield in grain crops (Harris et al 2007;Snape et al 2007;Thomas and Howarth 2000;Zheng et al 2009). Because the TaNAM-RNAi line exhibited delayed senescence in previous studies, we hypothesized that this line may also have delayed senescence under stress conditions, which would potentially result in improved yield under stress.…”
Section: Senescence and Yield Under Optimal And Stress Conditionsmentioning
confidence: 99%
“…Some SAGs are expressed under both natural and stressinduced senescence, while others are expressed exclusively during specific senescence conditions (Buchanan-Wollaston et al 2005; Van der Graaff et al 2006). Avoidance of leaf senescence during drought stress, a phenotype known as stay-green, is associated with grain yield in maize, wheat, and sorghum (Harris et al 2007;Snape et al 2007; Thomas and Howarth 2000;Zheng et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Three QTLs (quantitative trait loci), located on chromosomes 1AS (QSg.bhu-1A), 3BS (QSg.bhu-3B) and 7DS (QSg.bhu-7D) associated with stay-green character were found when recombinant inbred wheat lines (RILs) from the cross of the synthetic variety stay-green "Chirya 3" synchronized Indian cultivar 'Sonalika' were analyzed (KUMMAR et al, 2010). Mapping of QTLs in a maize segregating population (F 2 ) from contrasting parents for the stay-green character, resulted in 14 loci associated with stay-green and also high grain yield (ZHENG et al, 2009). …”
Section: Inheritance Of the Stay-green Charactermentioning
confidence: 99%